Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1016/j.cardiores.2007.05.029
|View full text |Cite
|
Sign up to set email alerts
|

A sphingosine kinase 1 mutation sensitizes the myocardium to ischemia/reperfusion injury

Abstract: Deletion of the SphK1 gene sensitizes the myocardium to IR injury and appears to impair the protective effect of IPC. These data provide the first genetic evidence that the SphK1-S1P pathway is a critical mediator of IPC and cell survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
67
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(73 citation statements)
references
References 37 publications
6
67
0
Order By: Relevance
“…Thus, the dramatic decrease of reperfusion injury caused by HDL and S1P may be due to both attenuation of endothelial dysfunction and inhibition of leukocyte extravasation through NO generation. In addition, HDL and S1P may have direct beneficial effects on the myocardium itself, on the basis of the following: (1) both agents protected cardiomyocytes against apoptosis in vitro and in vivo in the present study; (2) sphingosine kinase-1, the key enzyme in S1P synthesis, has been shown to mediate ischemic preconditioning in Langendorff hearts and its genetic deficiency sensitized the myocardium to ischemia/ reperfusion injury 31,32 ; and (3) several S1P receptors are present and functional in cardiomyocytes, 33 which suggests the possibility of direct receptor-mediated antiapoptotic effects. Thus, S1P may protect the heart by acting on both the endothelial cells and cardiomyocytes, and S1P 3 may be involved in both processes.…”
Section: Discussionmentioning
confidence: 67%
“…Thus, the dramatic decrease of reperfusion injury caused by HDL and S1P may be due to both attenuation of endothelial dysfunction and inhibition of leukocyte extravasation through NO generation. In addition, HDL and S1P may have direct beneficial effects on the myocardium itself, on the basis of the following: (1) both agents protected cardiomyocytes against apoptosis in vitro and in vivo in the present study; (2) sphingosine kinase-1, the key enzyme in S1P synthesis, has been shown to mediate ischemic preconditioning in Langendorff hearts and its genetic deficiency sensitized the myocardium to ischemia/ reperfusion injury 31,32 ; and (3) several S1P receptors are present and functional in cardiomyocytes, 33 which suggests the possibility of direct receptor-mediated antiapoptotic effects. Thus, S1P may protect the heart by acting on both the endothelial cells and cardiomyocytes, and S1P 3 may be involved in both processes.…”
Section: Discussionmentioning
confidence: 67%
“…Ϫ/Ϫ mice have defects in endothelial barrier functions and are more sensitive to heart injury (59,60). Furthermore, the SIPR agonist FTY720 blocks lymphocyte trafficking, prevents allograft rejection in renal transplants, and reduces multiple sclerosis burden in patients (46).…”
Section: Discussionmentioning
confidence: 99%
“…Even though S1P 2 regulates endothelial cell inflammatory responses (87), its functional significance in atherosclerosis has not been addressed. S1P is produced in the heart during brief periods of ischemia and protects the myocardium (119,120). It also activates the G protein-coupled inwardly rectifying potassium (GIRK) channels at the sinoatrial node and induces bradycardia (121).…”
Section: S1p In Diseasementioning
confidence: 99%